2020
DOI: 10.1101/2020.06.20.162255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How does the brain navigate knowledge of social relations? Testing for shared neural mechanisms for shifting attention in space and social knowledge

Abstract: How does the human brain support reasoning about social relations (e.g., social status, friendships)? Converging theories suggest that navigating knowledge of social relations may coopt neural circuitry with evolutionarily older functions (e.g., shifting attention in space). Here, we analyzed multivoxel response patterns of fMRI data to examine the neural mechanisms for shifting attention in knowledge of a social hierarchy. The "directions" in which participants mentally navigated social knowledge were encoded… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…This data-driven approach revealed a functional brain network responsive to perceiving high-SES compared to low-SES people, particularly in men. This network shows considerable overlap with a previously identified set of regions involved in status-based attention 6 , 67 and more broadly with networks believed to support salience detection 60 , 62 and attention 61 , 62 . However, the observed co-activation network extended beyond these core networks, possibly implicating broader domain-general networks supporting focused task engagement 62 65 .…”
Section: Discussionmentioning
confidence: 65%
“…This data-driven approach revealed a functional brain network responsive to perceiving high-SES compared to low-SES people, particularly in men. This network shows considerable overlap with a previously identified set of regions involved in status-based attention 6 , 67 and more broadly with networks believed to support salience detection 60 , 62 and attention 61 , 62 . However, the observed co-activation network extended beyond these core networks, possibly implicating broader domain-general networks supporting focused task engagement 62 65 .…”
Section: Discussionmentioning
confidence: 65%
“…Our proposal of a domain-general function of the SBN may appear at odds with reports of functional dissociations between subareas of this network (in particular the rTPJ-dmPFC network) that may be tuned to react in different ways to social versus non-social contexts 13,37,87 . This fine tuning of the type of information processed by subparts of the network does not rule out possible overarching functional mechanisms 53,88 , at the algorithmic level 52 . That is, different parts of a brain network may be specialized for processing different types of information but may still perform similar computations 51 .…”
Section: Social Cognition Re-expressed As Salience-based Stimulus Int...mentioning
confidence: 95%
“…However, orientation is not restricted to the spatial domain. It involves other domains such as the temporal and social ones (Du, Basyouni, & Parkinson, 2021; Parkinson, Liu, & Wheatley, 2014; Peer et al, 2015), that have been shown to be progressively impaired along the AD-continuum (Dafni-Merom, Peters-Founshtein, Kahana-Merhavi, & Arzy, 2019; Peters-Founshtein et al, 2018). Moreover, tests of orientation have been found to better discriminate between cognitively normal (CN) and mild cognitive impairment (MCI) participants (95% accuracy) when compared to standard neuropsychological evaluations (Addenbrooke’s Cognitive Examination (ACE) – 71%, Mini Mental State Examination (MMSE) – 70%) (Peters-Founshtein et al, 2018).…”
Section: Introductionmentioning
confidence: 99%